ABIOTIC FACTORS AS INDICATORS OF THE ABUNDANCE OF PENJAH FISH OF THE GOBIIDAE FAMILY IN THE MAPILLI RIVER ESTUARY, POLEWALI MANDAR DISTRICT, WEST SULAWESI - Fitri Fitri (Journal of Environmental Engineering and Sustainable Technology, 2019)
The aim of this study was to determine the effect of abiotic factors on the abundance of tilapia in the family of Gobiidae in the river of the Mapilli estuary. Sampling was carried out in two locations at three points each repeated three times. Samples were taken using a fish net by attaching to the edge of the river mouth and waiting for five minutes. Data collection for each station includes brightness, temperature, pH, salinity, current speed, conductivity, and the number of fish caught. The results showed that the abiotic factor had a significant influence on the abundance of penjah fish because at the time of abundance the migration season of fish heading to the estuary and in the Mapilli river had water conditions which were still suitable as a place to find food for Penjah fish when migrating. Abiotic factors that affect the abundance of anchovy fish in January, namely salinity, in March are influenced by current velocity, in April and May are influenced by temperature, current speed and brightness with the most abundant number of fish. Spread fish is the dominant species found in all locations and stations. The number of Penjah fish found during the research conducted over five months showed that the average appearance of anchovy fish fluctuated. The lowest abundance in February was 0, while the highest abundance occurred in April of 453 Tails.